2018
DOI: 10.1002/jctb.5626
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐layered TiO2 for effective bacterial disintegration of waste activated sludge and biogas production

Abstract: BACKGROUND Proper management of the huge amount of waste activated sludge generated during the conventional treatment of wastewater is nowadays a major environmental issue. Proper treatment of sludge needs huge investment and proper handling. To address this issue, the immobilized photocatalyst (TiO2) mediated exocellular fractionation of bacterial pretreatment for anaerobic digestion was utilized as a sludge treatment technique. RESULT Ti was deposited on glass substrate by a DC spluttering technique, and a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Slow or low biogas production was observed during the first week, accompanied by rapid production from the 5th to the 25th day, followed by steady production until the last week when the system was shut down. The slow production observed is in agreement with other reported works which suggest the microbes need to get acclimatised before they begin production [4,5,12]. The overall biogas production was enhanced by the MNP additives to the bioreactors as compared to the control system without any MNP additives.…”
Section: Digestate Degradation and Biogas Productionsupporting
confidence: 91%
See 2 more Smart Citations
“…Slow or low biogas production was observed during the first week, accompanied by rapid production from the 5th to the 25th day, followed by steady production until the last week when the system was shut down. The slow production observed is in agreement with other reported works which suggest the microbes need to get acclimatised before they begin production [4,5,12]. The overall biogas production was enhanced by the MNP additives to the bioreactors as compared to the control system without any MNP additives.…”
Section: Digestate Degradation and Biogas Productionsupporting
confidence: 91%
“…This is associated with the quality of the feedstock and the degree of degradation efficiency in the process, as well as the extent to which the post-treatment process was carried out. Significantly, sludge treatment contributes greatly to the total cost of wastewater treatment plants [4,5]. It was observed that the addition of MNPs to the bioreactors were easily separated from the sludge by an external magnet.…”
Section: Digestate Degradation and Biogas Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many oxidation techniques, including Fenton reactions [101]) and new reactions concerning peroxomonosulphate (PMS; [102]), nano-layered TiO 2 [103] and dimethyldioxirane (DMDO), can cause the alteration of refractory organic matter into easily accessible and soluble biochemical oxygen demand (BOD), and subsequently improve the biogas yield [88] (Table 2). Recently, a newly greener oxidant for this purpose, peracetic acid (PAA), has been proposed to improve anaerobic digestion [104].…”
Section: Chemicalmentioning
confidence: 99%